PENERAPAN TEKNOLOGI SUPLEMENTASI BERBASIS DAUN KELOR DAN MOLASES PADA PETERNAKAN KAMBING RAKYAT - Soetanto, H.; Marhaeniyanto, E.; Chuzaemi, S. (Universitas Tribhuwana Tunggadewi, 2011)
The objectives of this study were 1) to evaluate the diversity of forages commonly fed to goats in Pasrujambe village; 2) to introduce moringa leaves as a protein source for growing goats under village management conditions. Ninety goat farmers were surveyed on the profiles of goat farming and the diversity of forages offered to their goats during the dry season. To evaluate the impact of moringa leaves supplementation, 26 growing goats (less than one year old) were alloted into two unequal groups, that is control group (7 heads) and supplemented group (19 heads) for four months during which observations on feed intake, daily gain and feed conversion were taken place. The results indicates that most goat farmers (73,3%) have been practising more than 25 years, while the rest (26,7%) was keeping goats less than 5 years. The sex ratio of goats kept by the farmers was 67,4% female: 32,6% male. There were 49 species of forages commonly fed to goats in Pasrujambe that can be grouped into 5 species of grasses, 3 species of tree legumes, 29 species of tree leaves and 12 species of herbaceous. There were significant improvement in feed intake (P